A Assessment of Nurses’ knowledge in the early detection and Management of acute kidney injury in Assuit and Mansoura Main University hospital: Assessment of Nurses’ knowledge in the early detection and Management of acute kidney injury - Abdou, Fayza Ahmed; Abdou, Shimaa Mohammed (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: Acute kidney injury (AKI) is a serious clinical problem for all hospitalized patients especially critically ill. AKI is worldwide health concern which is preventable. For that reason, the nurses’ knowledge and awareness of AKI would improve the early recognition of all suspected and real cases on a timely basis. Objective: assess the nurses’ knowledge in the early detection and management of acute kidney injury in Assuit and Mansoura Main University hospital. Research question: what is the nurses’ knowledge in the early detection and management of acute kidney injury? Research design: descriptive research design was used in this study. Setting: This study was conducted in general intensive care unit and surgical ward in two hospitals namely: Assuit Main University and Mansoura Main University hospital. Subjects: A convenient sample of approximately 100 nurses working in previous mention setting and provide patient care were included in this study and the period of data collection from 30th August 2018 to 30th November 2018. Results: Total mean nurses’ knowledge score regarding AKI in Assuit and Mansoura hospital poor and the statistically significant difference between both groups regarding pathophysiology, medical and nursing management of AKI. Conclusion: The findings of the present study show that the level of nurses’ knowledge regarding AKI in both hospitals was generally poor. Keywords: Nurses’ knowledge, early detection, management, AKI